CORRECTION OF IMMUNOSUPRESSION IN CANCER PATIENTS DEPENDING ON THE TYPE OF ANESTHESIA (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The conducted comparative assessment of the effectiveness of the proposed treatment and diagnostic algorithm for the correction of perioperative immunosuppression in cancer patients showed its high clinical effectiveness. The use of immunocorrection before surgery provided a significant improvement in the indices of both cellular and humoral immune responses, with a limitation of the severity of the inflammatory cascade, a decrease in the level of proinflammatory cytokines and stabilization of the activity of regulatory links.